Penulisan Surat Dinas dan Pengelolaan Arsip Sekolah bagi Tenaga Kependidikan Se-Cabdin Wilayah VII Provinsi Sumatera Barat - Elva Rahmah; Marlini Marlini; Emidar Emidar; Zulfikarni Zulfikarni; Ermawati Arief (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
The purpose of community service activities is to improve the ability of educational staff in making official letters and managing school archives. The target of this activity is the education staff of SMA/SMK/SLB di Dinas Pendidikan Cabang Wilayah VII Provinsi Sumatera Barat. In this activity, problems will be completely solved related to the making of official letters and the management of school archives to realize school accountability. The approach used in implementing community service programs is Participatory Rural Appraisal (PRA) which emphasizes partner participation in all activities, from planning, implementation, and evaluation. The output target in the form of a process is an increase in the ability of the target audience in understanding the concept and process of making official letters and managing school archives. The results of the training and mentoring activities carried out are expected to create school archives that are systematically organized so that the school and the education office can access the archives easily and quickly.